2023
DOI: 10.3390/life13091820
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking the Hidden Danger: A Decade-Long Systematic Review of Case–Control Studies on Single Occupational Risks and Prostate Cancer

Caterina Ledda,
Massimo Bracci,
Alba Spadafora
et al.

Abstract: The present systematic review addresses the influence of occupational exposures on prostate cancer risk. Eleven studies were analyzed for a range of occupational exposures, including but not limited to firefighting, physical activity, night shift work, chemical exposure, and solar ultraviolet radiation. The results of the review reveal that firefighters exposed to harmful substances, individuals engaged in physically strenuous work, and workers with chronic night shift routines showed an increased likelihood o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…Numerous reports have found that cadmium inhalation leads to respiratory cancers including tracheal cancer, bronchus cancer and lung cancer [ 9 - 11 ]. Additionally, occupational exposure to Cd is known to have adverse effects on the prostate [ 12 , 13 ]. Cd absorbed through the respiratory system can circulate through the bloodstream and reach the prostate ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have found that cadmium inhalation leads to respiratory cancers including tracheal cancer, bronchus cancer and lung cancer [ 9 - 11 ]. Additionally, occupational exposure to Cd is known to have adverse effects on the prostate [ 12 , 13 ]. Cd absorbed through the respiratory system can circulate through the bloodstream and reach the prostate ( Fig.…”
Section: Introductionmentioning
confidence: 99%